Development of Three-Dimensional Based Smart Box Media to Train Students’ Listening Skills - Milatullatifah, Aam; Yuliana, Rina; Hilaliyah, Tatu (LPPM Universitas Primagraha, 2024)
Students' success in understanding and mastering lessons begins with good listening skills. This research aims to create three-dimensional based smart box media. The research method used in this research is Research and Developments with the Sugiyono development model. The results of this research can improve students' listening skills by obtaining an average score from media experts of 94% (Very Decent), an average score from material experts of 91% (Very Decent), while an average score from linguists is 90 % (Very Decent). And the student response results were 93% (Very Good). Therefore, Three Dimensional Based Smart Box Media to train students' listening skills in elementary schools is very feasible and very good for use in the learning process of students in fourth grade elementary school.